Lack of microbiota reduces innate responses and enhances adaptive immunity against Listeria monocytogenes infection. Issue 6 (20th March 2014) - Mittrücker, Hans‐Willi; Seidel, Daniel; Bland, Paul W.; Zarzycka, Agnieszka; Kaufmann, Stefan H. E.; Visekruna, Alexander; Steinhoff, Ulrich
<x xml:space="preserve">Abstract</x> The intestinal microbiota influences not only metabolic processes, but also the mucosal and systemic immune systems. Here, we compare innate and adaptive immune responses against the intracellular pathogen Listeria monocytogenes in germfree (GF) and conventional mice. We show that animals without endogenous microbiota are highly susceptible to primary infection with impaired activation and accumulation of phagocytes to the site of infection. Unexpectedly, secondary infection with otherwise lethal dose resulted in survival of all GF animals which cleared bacteria more rapidly and developed a stronger antilisterial CD8+ memory T‐cell response compared to conventional mice. In summary, lack of the intestinal microbiota impairs early innate immunity, but enhances activation and expansion of memory T cells.